Faktor-Faktor Yang Berhubungan Dengan Skrining Human Immunodeficiency Virus (HIV) Pada Ibu Hamil Di Puskesmas Kolongan Kabupaten Minahasa Utara - Michaella Louisa Korah; Afnal Asrifuddin; Grace Debbie Kandou (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Background: Human Immunodeficiency Virus (HIV) remains a major public health problem affecting both mothers and children due to the risk of mother-to-child transmission during pregnancy, childbirth, and breastfeeding. HIV screening among pregnant women is an essential strategy to prevent vertical transmission. Objective: This study aimed to analyze the association between maternal knowledge, family support, and HIV screening among pregnant women at Kolongan Community Health Center, North Minahasa Regency. Methods: A quantitative study with a cross-sectional design was conducted from February to May 2026. Eighty pregnant women were selected through purposive sampling from a population of 473 pregnant women. Data were collected questionnaires and analyzed using univariate analysis and Spearman rho correlation test. Results: Most respondents had good knowledge (mean=3.69) and received good family support (mean=39.71). Bivariate analysis showed a significant association between maternal knowledge and HIV screening (p=0.030; r=0.242), as well as between family support and HIV screening (p<0.001; r=0.385). Conclusion: Maternal knowledge and family support were significantly associated with HIV screening among pregnant women. Suggestion: Strengthening health education and involving family members, particularly husbands, are recommended to improve HIV screening coverage among pregnant women.